Light Induced Hydrogen Production From Ethanolic Aqueous Solutions Sensitizzed By 2,4-Dimetboxy Benzylidene-2- Hydroxy Aniline And Some of Its Metal Complexes - Abdul- Ghani, A..J.; Tapabashi, N. 0. R. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Hydrogen productions were achieved by irradiating ethanol ic aqueous solutions (20%. v/v) containing mixtures of the ligand 2,4- dimethoxybcnzylidene-2-hydroxy aniline (HL) or one of i ts complexes (ML2) wi th the following divalent ions: fVbl (II), Fc(IT), Co(II). Ni( rt ), Cu(H) and Zn (11), as photosensi1izers, methyl viol ogen (MY.:-) as electron acceptor. ethylene diamine tetraacctic acid disodium saJt (EDTA) as a sacrificial electron donor. in presence of platinum poly (viny l akohol) (Pt-PVA) or platinized li02 (Pt/Ti02). (200 and 45 micron) as reduction catal ysts. using white light from 250 W xenon a rc lamp at room temperature 25Â±2 Â°C. Oxidation Potentials of the ligand and its complexes were determined by cyclic vultammetry. The efficiency of the photoreduction of lv1V2+ and hydrogen production .by HL and metal .complexe.s was main l y dependant on pH , type- and particle size of cata lyst, as well as meLal ion in case of ML2. Best pertormances were recorded by the free ligand.